The Effect of Fair-value Accounting on the Value Relevance of the Balance Sheet and the Income Statement - Zaki Mashoka, Tareq (Jordan Journal of Business Administration, 2022)
The aim of this paper is to examine the value relevance of the balance sheet and the income statement. Specifically, this paper investigates the value relevance of book value of equity compared to the value relevance of earnings in firms that depend more on fair-value accounting. The sample of the study includes all listed firms in the Amman Stock Exchange (ASE), which are classified into two main groups: financial firms and non-financial firms. The results show that the value relevance of the balance sheet for financial firms is higher than that for the income statement. The results also show that firms with lower financial assets depend more on historical accounting and have higher-relevance income statements. The results indicate that the higher the percentage of financial assets, the more the firm depends on fair-value accounting and consequently, the balance sheet becomes more value-relevant to investors compared to the income statement.